Determination of resorption surface areas of bone sample - Margasanti Wijaya. (2009)
As a dynamic process, bone is constantly being remodelled. The remodelling is due to either osteoblasts (bone formation) or osteoclasts (bone resorption). The quantifying of bone resorption area is very important and critical for bone treatment. However, the quantization of bone resorption using current biomedical technology is still very tedious, time consuming, and very expensive. In justifying the easiest and cheapest way to measure bone resorption area, numerous optical methods are studied and developed. One of the cheapest methods with no direct contact measurement is the optical method. In this report, optical method, Phase Shifting Interferometer (PSI), is developed to study the resorption area of the bone sample in three dimensions (3-D). The main concept here is that a time-varying phase shift is introduced between the interference pattern of the reference beam and the test or sample beam in the interferometer. Two algorithms in PSI, the Carre and Hariharan algorithms, will be developed and compared to improve the reading’ s accuracy. The results from Optical measurement for three different samples (Silicon, Aluminium, and Bone) are then compared with the direct physical measurement result, the Surface Profiler, in two dimensions (2-D). The depth of the pit area will be compared as to know the accuracy of Optical method (PSI) versus direct contact measurement (Surface Profiler).